Masa Kemunduran Pendidikan Islam : Analisis Dampak Runtuhnya Baghdad pada Tahun 1258 M - A. Riswan Pratama; Eka Wahyuni; Fatimah Az Zahra; Mahfud Ifendi (Jurnal Budi Pekerti Agama Islam, 2025)
Islamic education reached its peak during the Abbasid Dynasty, precisely from the eighth to the thirteenth centuries AD. This period is often referred to as the "Islamic Golden Age", during which Baghdad, the capital of the Abbasids, became the center of world knowledge and culture. The purpose of this study is to analyze the glory of Islamic education before the collapse of Baghdad, the factors that caused the collapse of Baghdad, and analyze the impact and efforts to revive Islamic education. The benefits of this article are expected to provide an in-depth understanding of the relationship between the collapse of the center of Islamic civilization and the decline of education, as well as provide relevant historical insights to rebuild the glory of Islamic education in modern times. The author uses a qualitative method with the type of library research, the main sources of data in this research are books and websites relevant to Islamic history, as well as scientific journal articles that discuss Islamic history from various perspectives, both published in national and international journals. The data obtained will be analyzed qualitatively with a descriptive approach to identify the main themes and gain a better understanding of the Decline of Islamic Education: An Analysis of the Impact of the Fall of Baghdad in 1258 AD. The fall of Baghdad in 1258 AD became one of the most tragic events in the history of Islamic civilization, especially in the field of education. The destruction of the city resulted in the loss of educational centers, such as Baitul Hikmah, as well as valuable manuscripts and scientific works. The disconnected scientific tradition and intellectual stagnation are a long-term impact felt by the Islamic world. After the fall of Baghdad, many scholars took an important role in efforts to revitalize Islamic education. They moved to new territories, bringing with them the science and scientific traditions of Baghdad.